2022
DOI: 10.1177/09567976221081872
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Appreciated Buffers Against the Negative Effects of Unequal Division of Household Labor on Relationship Satisfaction

Abstract: Decades of research from across the globe highlight unequal and unfair division of household labor as a key factor that leads to relationship distress and demise. But does it have to? Testing a priori predictions across three samples of individuals cohabiting with a romantic partner during the COVID-19 pandemic ( N = 2,193, including 476 couples), we found an important exception to this rule. People who reported doing more of the household labor and who perceived the division as more unfair were less satisfied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Given that stressors can occur both internal and external to the relationship (see Barton et al, 2015;Randall & Bodenmann, 2009), protective effects of the two forms of gratitude were investigated with respect to ineffective arguing (an internal stressor) and financial strain (external stressors). Also consistent with prior research (e.g., Barton et al, 2015;Gordon et al, 2022), we hypothesized that perceiving gratitude from one's partner would elicit a protective-stabilizing effect (Luthar, 1993) for ineffective arguing, such that heightened levels of ineffective arguing would not be associated with worsened relationship outcomes among individuals reporting higher levels of perceived gratitude from their partner. We did not hypothesize protective effects involving financial strain given the lack of significant moderation effects found in prior research (Barton et al, 2015).…”
Section: The Current Studysupporting
confidence: 58%
See 1 more Smart Citation
“…Given that stressors can occur both internal and external to the relationship (see Barton et al, 2015;Randall & Bodenmann, 2009), protective effects of the two forms of gratitude were investigated with respect to ineffective arguing (an internal stressor) and financial strain (external stressors). Also consistent with prior research (e.g., Barton et al, 2015;Gordon et al, 2022), we hypothesized that perceiving gratitude from one's partner would elicit a protective-stabilizing effect (Luthar, 1993) for ineffective arguing, such that heightened levels of ineffective arguing would not be associated with worsened relationship outcomes among individuals reporting higher levels of perceived gratitude from their partner. We did not hypothesize protective effects involving financial strain given the lack of significant moderation effects found in prior research (Barton et al, 2015).…”
Section: The Current Studysupporting
confidence: 58%
“…The protective effects of gratitude for financial strain, however, were non-significant. Other research has found that perceived gratitude (i.e., feeling appreciated) buffered relationship quality against the negative effects of attachment insecurity (Park, Impett, et al, 2019) and unequal division of household labor (Gordon et al, 2022). Although providing important preliminary insights for this area, these studies have only considered gratitude from one’s partner and with rather homogenous samples of predominantly White, well-educated individuals.…”
Section: The Protective Effects Of Gratitudementioning
confidence: 99%
“…The COVID-19 pandemic introduced a host of external stressors that have led to increased loneliness, stress, financial strain, and worry about COVID-19, and spilled over into people's relationships and interest in sex. More specifically, stay-at-home orders, which were mandated throughout the world to mitigate the spread of COVID-19 (Koo, Cook, & Park, 2020;Lewnard & Lo, 2020), involved drastic changes to people's daily activities, and resulted in many people social distancing together with their romantic partner for an extended period of time, often both working and caring for children from home (Carlson, Petts, & Pepin, 2020), having to balance work, household responsibilities and childcare (Gordon, Cross, Ascigil, Balzarini, Luerssen, & Muise, 2022). The COVID-19 pandemic also had economic consequences with spikes in the unemployment rate worldwide leading to levels of unemployment that were higher than the Great Recession and Great Depression (Faria e Castro, 2020; Kochhar, 2020;Pappas, 2020).…”
Section: Covid-related Stressors and Sexual Desirementioning
confidence: 99%
“…For example, despite the attention paid to it (e.g., Waddell et al., 2021), division of labor during the pandemic did not emerge as an important predictor of relationship satisfaction in these samples. This may be because the association between division of labor and relationship satisfaction depends on how appreciated people feel (Gordon et al., 2022), a factor that did emerge as an important predictor. Our findings are also inconsistent with another machine learning project that identified attachment as a top predictor of relationship quality at the beginning of the pandemic (Eder et al., 2021).…”
Section: Discussionmentioning
confidence: 99%